Positive effects of thyroid replacement therapy on assisted reproductive technology outcomes in women with subclinical hypothyroidism with positive thyroid peroxidase autoantibodies - Himanshu Arora, Ph.D; Ineabelle Collazo, B.S; Katherine L. Palmerola, M.D; Madhumita Parmar, B.S; Manish Narasimman, B.S; Nicholas Hendon, B.S; Juergen Eisermann, M.D; Maria Bustillo, M.D (Elsevier, 2022)
Objective: To study the beneficial effects of thyroid replacement therapy (TRT) on pregnancy outcomes in patients with subclinical hypothyroidism (SCl hypoT) with respect to thyroid peroxidase (TPO) autoantibodies. Design: Retrospective study of 706 patients. Setting: Not applicable. Patient(s): The study evaluated 706 patients, who were divided into 3 cohorts: euthyroid patients, with pre-in vitro fertilization thyroid-stimulating hormone levels of <2.5 μIU/mL; patients with SCl hypoT, defined as thyroid-stimulating hormone levels of >2.5 μIU/mL and <4 μIU/mL, who were not treated; and patients with SCl hypoT who received TRT. The 3 cohorts were further subclassified into 2 groups, each based on TPO antibody levels. Intervention(s): The cohorts were compared for the effects of TRT on pregnancy outcomes. Main Outcome Measure(s): Identification of effects of TRT on assisted reproductive technology outcomes. Result(s): Patients with SCl hypoT had significantly fewer positive pregnancy outcomes than euthyroid patients. Importantly, low-dose TRT was found to be beneficial in improving IVF success and pregnancy outcomes in patients with SCl hypoT. The original cohort of patients, further classified into 2 subgroups on the basis of antithyroid (TPO) antibodies, showed that low-dose TRT was associated with improved pregnancy outcomes in women with SCl hypoT and TPO-positive antibodies. Conclusion(s): Our findings demonstrate that low-dose TRT may be beneficial in improving in vitro fertilization success and pregnancy outcomes in women with SCl hypoT and TPO-positive antibodies.